IMPLICATIONS OF LONG DISTANCE MARRIAGE ON STUDENT LEARNING MOTIVATION (Case Study at STDI Imam Syafi'i Jember) - Ardian Bagus Armadi; Sabilul Muhtadin (Universitas Nurul Jadid, 2025)
Humans are social beings who in essence cannot live and meet their own needs. One manifestation of humans as social creatures is to get married. The couple Long Distance Marriage (LDM) who decided to live in different places and separated by distance cause each individual to need a role that should be obtained by a partner who lives one roof. Long Distance Marriage (LDM) will also interfere with the concentration of students in receiving education in lectures and motivation that tends to be unstable. This study aims to analyze the factors causing the occurrence of long distance marriage and impact as well as efforts made by STDI Imam Syafi'i students in maintaining learning motivation. This study uses a qualitative approach with the type of case study research. Factors causing the occurrence of long distance marriage in STDI students academic factors, economic factors, and work factors. Negative impacts include difficulty focusing, emotional burden, difficulty setting time. The positive impact includes better time management, motivation to complete studies. Solutions for couples Long Distance Marriage in maintaining their learning motivation include routine contacting couples, asking for family support, letting intentions, manage time well..